EFEKTIVITAS PELAKSANAAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI NAGARI SIBARAMBANG - Agusman Agusman; Elimartati Elimartati (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
Marriage after the marriage contract hopes to get peace, happiness. Underage marriages are marriages carried out under the age of 19. Law No. 16 of 2019 article 7 paragraph (1) "Marriage is only permitted if the man and woman have reached the age of 19 years.". then the author also found that there were many divorced couples in Nagari Sibarambang after law number 16 of 2019 was passed. The purpose of changing the law is to suppress divorce. Based on this phenomenon, the author is interested in researching this problem in the form of a thesis entitled "The effectiveness of the implementation of Law Number 16 of 2019 amendments to Law Number 1 of 1974 concerning Marriage in Nagari Sibarambang, District X Koto Above, Solok Regency)". The type of research in this research is field research using a qualitative descriptive approach. The results of this study show that the implementation of law number 16 of 2019 concerning marriage have not been effective even though socialization has been carried out, this is not all people know about changes to the law, the nagari guardian is only as capable as possible in providing information. It can be seen that there are still many people who carry out underage marriages, they think they are still using the old law, namely Law No. 1 of 1974.